A94 BARRIERS TO ADVANCEMENT ALONG THE GASTROENTEROLOGY CAREER PATHWAY: A RESIDENT PERSPECTIVE. (4th March 2021) - Pattni, C; Jawaid, N; Bollegala, N
Abstract: Background: GI residency training programs in Canada are comprised of approximately 30% females. Survey data from procedural specialities reveal gender related differences relating to work-life balance, parental obligations, access to role models, and workplace gender discrimination. Aims: To determine gender specific differences affecting the choice of GI as a sub-specialty and the experience of GI as a career during residency and fellowship. Methods: A 91-question mixed methods survey was electronically disseminated in two recruitment waves to PGY4-6 gastroenterology residents and fellows across Canada between May 7 th -July 1 st, 2020. The survey consisted of nine groups of questions aimed at understanding personal, professional, financial, and training characteristics. Comparisons were made between self-identified male and female genders. Wilcoxon (Mann Whitney U test) was used for continuous variables while chi-squared test and fisher's exact test was applied for categorical variables using SAS software. Qualitative thematic analysis was applied for short answer responses with two independent reviewers. Results: A total of 122 residents were surveyed with a response rate of 36% (44/122).There were 17 PGY4s, 15 PGY5s, and 12 PGY6s. Females comprised 41% (18/44) of respondents. Women were statistically more likely to take on a predominant caregiver role for children (p=0.012) and state that having children would slow their career advancement (p=0.046). Men were more likely to state that it is preferable to have children during residency (p=0.036) and that their partner's preference factored into their subspecialty training choice (p=0.009) than women. Male PGY4/5 trainees were more likely to select therapeutic endoscopy for advanced training (p=0.033). No statistical difference was found regarding aspirations for administrative/leadership positions, desired future income, practice setting, academic pursuits, and perspectives on compromising marriage for career. Qualitative analysis suggests non-gender specific challenges related to achieving work-life balance, securing a desired location of practice, and obtaining financial stability are common resident and fellow concerns. Conclusions: Our study is the first of its kind within the field of gastroenterology to focus on GI residents and fellows' experiences within Canadian training programs. Our results show that there exist gender related differences in relation to work-life balance and career advancement. Women may benefit from supports to cope with increased caregiver demands in order to allow them to meet career goals which are similar to their male peers. Funding Agencies: None